2012
DOI: 10.1097/shk.0b013e31826ae951
|View full text |Cite
|
Sign up to set email alerts
|

Gene Polymorphisms in the Heme Degradation Pathway and Outcome of Severe Human Sepsis

Abstract: Heme and its breakdown products CO, Fe, and bilirubin are being recognized as signaling molecules or even therapeutic agents, but also exert adverse effects when released at high concentrations. Manipulating the pathway confers protection in rodent sepsis models via both control of free heme and formation of its first and higher-order products. Thus, regulatory elements present in human heme oxygenase 1 (HMOX1) and biliverdin reductases (BLVRA/B) genes might impact outcome. We tested whether a highly polymorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…The A(-413)T SNP can affect HO-1 promoter transcriptional activity and disease outcomes, 9 albeit less so than the HO-1 (GT) n repeat length. [10][11][12] The frequency of the "T" A(-413)T SNP was significantly higher in African Americans than in European Americans (66.0% vs 41.8%), whereas the frequency of the "A" SNP was lower (34% vs 58.2%) (figure 1E), and, as expected for Hardy-Weinberg equilibrium, the TT and AT genotypes were more prevalent in African Americans (figure 1F). Also, the A(-413)T SNP and the HO-1 (GT) n allele genotypes were not independently expressed; the "A" SNP associated with medium "M" HO-1 (GT) n alleles, whereas the "T" SNP associated with both short "S" and long "L" HO-1 (GT) n alleles (not shown).…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…The A(-413)T SNP can affect HO-1 promoter transcriptional activity and disease outcomes, 9 albeit less so than the HO-1 (GT) n repeat length. [10][11][12] The frequency of the "T" A(-413)T SNP was significantly higher in African Americans than in European Americans (66.0% vs 41.8%), whereas the frequency of the "A" SNP was lower (34% vs 58.2%) (figure 1E), and, as expected for Hardy-Weinberg equilibrium, the TT and AT genotypes were more prevalent in African Americans (figure 1F). Also, the A(-413)T SNP and the HO-1 (GT) n allele genotypes were not independently expressed; the "A" SNP associated with medium "M" HO-1 (GT) n alleles, whereas the "T" SNP associated with both short "S" and long "L" HO-1 (GT) n alleles (not shown).…”
Section: Resultsmentioning
confidence: 66%
“…6 An A(-413)T SNP can affect HO-1 promoter transcriptional activity and disease outcomes, 9 albeit less so than the HO-1 (GT) n repeat length. [10][11][12] Short HO-1 (GT) n repeat alleles associate with better outcomes in inflammatory and oxidative stress-associated diseases, 7,8,[13][14][15] and the prevalence of these short alleles differs significantly among different populations. We recently determined HO-1 (GT) n alleles in individuals in an HIV autopsy cohort (n = 554) and showed that the presence of 1 or more short HO-1(GT) n alleles associated with a lower risk of HIV encephalitis and less brain inflammation (type I interferon responses and T-cell activation).…”
mentioning
confidence: 99%
“…There exists ample evidence supporting a role for genetic variation of human HMOX1 to impact outcome. In particular, the single nucleotide polymorphism (SNP) rs2071746 and a microsatellite (GT-dinucleotide repeat, (GT) n ) in the promoter region of the gene are associated with incidence, progression, or outcome of various clinical diagnoses as diabetes, sepsis, ARDS, myocardial infarction, and failure of kidney and liver grafts [610]. These polymorphisms might be an intrinsic component of the pathogenesis of some of these cases via HMOX1 transcription and/or translation regulation and subsequent HO-1 activity [3].…”
Section: Introductionmentioning
confidence: 99%
“…Both polymorphisms are in strong linkage disequilibrium [10,13]. The pattern of the (GT) n distribution has been shown to be trimodal with 23, 30 and 37 repeats (named here as N23, N30, N37) as major alleles within the three length classes [10]. Although there have been correlations between (GT) n length and HO-1 expression reported, these data remain not coherent.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental and clinical studies suggest that HMOX1 is the rate-limiting step of heme degradation, and that its genotypes and underlying regulatory mechanisms are associated with the outcome in sepsis. [44][45][46][47] The particular design of the present study with purposeful selection of patients for the discovery set (secondary sepsis vs. systemic inflammation without infection) and consecutive validation of candidates in the total cohort by an independent method has been conceptualized to overcome possible masking effects by ''non-selective'' whole-genome screening of all patients. In contrast to our results, gene expression patterns in a similar trauma patient cohort in a previous study by the Glue grant consortium were found to be more common than different in patients with ''complicated'' or ''uncomplicated recovery.''…”
Section: Discussionmentioning
confidence: 99%